Indirect subjects : Nollywood's local address - Brown, Matthew H., 1979- (Duke University Press, 2021)
"In Indirect Subjects, Matthew H. Brown argues that screen media can play spatial roles in global power relations. Brown focuses on Nollywood, Nigeria's commercial film industry, which emerged in the 1990s, but places it in the context of other local screen media, particularly state television, which has been a feature of Nigerian culture since the 1960s."--